The Role Of Managerial Economics In Increasing Competitiveness In UMKM Derizqi Qua - Kurniasih, Nining; Hermiyanti, Aprillya; Qauly, Dzikry; Pogially, Farandika (Journal of Bussines Management Basic, 2026)
This article analyzes the Derizqi Qua UMKM, a refillable drinking water business established in 2021, using a growth strategy approach. The analysis was conducted through a review of internal factors such as human resources, filtration technology, operations, marketing, and financial conditions, as well as external factors including political, economic, socio-cultural, technological, legal, and environmental aspects. The analysis shows that Derizqi Qua excels in water quality, customer service, and the use of modern equipment. However, it still faces several challenges such as ineffective promotion, manual record-keeping, limited workforce, intense competition, and limited capital. Based on these findings, relevant growth strategies, including market penetration, market development, product development, and diversification, are proposed to increase competitiveness and business sustainability. The implementation of these strategies is expected to help Derizqi Qua UMKM develop in a targeted and sustainable manner.